Importance of Hadi̇th and Secti̇ons of the Sci̇ence of Hadi̇th - Guliyev, Ibrahim (Scholarya Demo Journal of Ruby, 2019)
Hadithology is one of the most useful and widely used Islamic sciences. Those who study the hadiths, as well as their history and methodology become more familiar with Islamic culture, and learn the true teachings of Islamic faith through the knowledge of Islam. One of the most important benefits of the aforementioned science is to gain greater knowledge of the Holy Qur’an. It is well known from the history of Islam that Prophet Muhammad (PBUH), his companions and faithful companions after him, explained the deep Matlab, the organized (difficult to understand) meanings in the Holy book revealed by Allah Ta’ala to Muslims in a very simple but scientific way. This is how the Qur’an declares this: “And We have not sent any Messenger except with the language of his people in order that He might make things clear to them” (The Holy Qur’an 1991, Surah İbrahim, Verse 4). And Almighty Allah says in another verse that: “And we revealed to you the message that you may make clear to the people what was sent down to them and that they might give thought.” (The Holy Qur’an 1991, Surah An-Nahl, Verse 44). Thus, the article consists of two parts. In the first part, readers were told about the importance of hadith in religion. That is why Islamic scholars have turned to the Hadith and Sunnah as the second source after the Qur’an in solving religious issues. In this case, of course, it is necessary to determine the authenticity (exactness) of the existing Hadith. The second part of the article is about the sections of the science of hadith. The most famous works written in the field of Hadith studies, along with the history of their creation and development, have been presented here.